The waves eaudiobook - Woolf, Virginia (Recorded Books Inc., 2014)
Six children - Bernard, Susan, Rhoda, Neville, Jinny and Louis - meet in a garden close to the sea, their voices sounding over the constant echo of the waves that roll back and forth from the shore. The book follows them as they develop from childhood to maturity and follow different passions and ambitions; their voices are interspersed with interludes from the timeless and unifying chorus of nature. Widely regarded as one of Woolf' s greatest and most original works, The Waves conveys the rhythms of life in synchrony with the cycle of nature and the passage of time